Kontribusi Partisipasi Kerja Berbasis Gender dan Kepadatan Penduduk terhadap Petumbuhan Ekonomi di Sulawesi Selatan - Dedi Mardianto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
Economic growth is a description of the economic activities of a region in a continuous manner towards better economic activities in a certain period, so this discussion aims to analyze the influence of gender-based work pertypi and population density on economic growth in South Sulawesi by using time series and cross section data sourced from the Central Statistics Agency from 2018 to 2022. The method used in this discussion is using a quantitative method with a panel data regression analysis approach. The results of the study show that the gender-based work participation variable has a significant positive effect on economic growth in South Sulawesi and the variable of seat density has a significant negative effect on economic growth in South Sulawesi. Meanwhile, simultaneously gender-based work participation variables and population density have a significant impact on economic growth in South Sulawesi. So this result shows that the government must continue to encourage work participation for both men and women through the provision of jobs.